Det kompakte bosted - Munkejord, Mai Camilla (Tidsskrift for kulturforskning, 2009)
Statistics show that more than 25% of the population in Finnmark, in the north of Norway, is born outside the county. Interestingly though, hegemonic discourses in research and politics have focused nearly exclusively on the high out-migration from Finnmark. The newcomers and their stories about living in the north have received very little attention. This paper is a part of my on-going PhD-project, where I focus on in-migrants in two places in Finnmark, Vadsø and Havøysund. In 2005 I did five months of fieldwork there, as well as interviews with 25 women and 25 men from 31 in-migrant households. Several recent studies focus on how rurality is constructed by women and men by examining their representations of how it is to live in a place defined as rural. A gap in Norwegian rurality studies, however, is that the coast-inland dimension, as well as the North-South dimension, are omitted. This paper attempts to fill this gap by analysing what we may call in-migrants' representations of northern coastal ruralities. The paper hereby challenges established understandings of rurality in research in Norway, and suggests new metaphors to grasp in-migrants' sense of place in the rural North, such as "compact materiality", "short distances", "an easy, practical everyday life" with possibilities of "flexible belonging."